Tech Talk. Elementary: Student's Book - Hollett V. Vicki (Oxford Business English)
Tech Talk is a practical three-level course for adult learners in the technical, industrial, and scientific sectors who need English for everyday communication at work. Tech Talk gives learners the language they need for real-life, hands-on tasks like checking specifications, suggesting a solution, explaining functionality, or offering help. From maintenance to customer service, and from manufacturing to technical support, the focus is always on getting the job done. Tech Talk offers: practical speaking activities based on real workplace scenarios, key vocabulary for use in a wide range of situations, a straightforward, need-to-know approach to grammar, regular reviews and updates, information and ideas for non-specialist teachers.The Tecri Talk package includes: this Student's Book, a Teacher's Book with teaching notes and answer key, a Workbook with further practice of key vocabulary and useful phrases, an Audio CD, plus online tests and additional materials.